As práticas de ensino religioso na perspectiva emancipatória: uma abordagem de Paulo Freire. - Paixão, Maria Edjane (2017)
The study reflects about practices of Religious education on a advanced perspective, illustrates conceptions to a foundation of this practices. We reflect about a reality of the world Post-Modern, understand that face this reality require a citizen formation that set free, this imply, to be critic and participatory to face the world replete of contradictions and a change of values, imposing to men and women a subordinate situation in front of capitalist system. The research relates a espistemological conception of Religious education to the practices of education that enable students the critical formation about reality/world. We assume the principle that Education Religious –ER has a historical reality that places it as the teaching of a single religion, which changes after republic, from understanding of Secular State. This Job has how porpuse reflect the practices of ER on an approach of Sciences of the Religious, because it helps the understanding of the religious phenomenon interdisciplinary and trandisciplinary perspective. Think about the practices of education on a epistemological conception remit to us Freireana approach, more specifically the Victim Pedagogy. The study show to us that practices od education on a advanced perspective requires enlargement of docent formation to an increase in value of component Religious Education and fundamentally to effectuation of practices that helps the subjects formation free, autonomic and engaged to a fair, ethical and equitable society social.